2016
DOI: 10.1017/s0007485316000201
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and social interactions of the Argentine ant Linepithema humile change with sucrose concentration

Abstract: Liquid sugar baits are well accepted by the Argentine ant Linepithema humile and are suitable for the chemical control of this invasive species. We evaluated how sugar concentrations affect the foraging behavior of L. humile individuals. We quantified feeding variables for individual foragers (ingested load, feeding time and solution intake rate) when feeding on sucrose solutions of different concentrations, as well as post-feeding interactions with nestmates. Solutions of intermediate sucrose concentrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 58 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Ingestion volume from hydrogels decreased as sucrose concentration increased, consistent with results of L. humile and other ant species feeding from liquid droplets. 18,23,24 However, ants spent less time feeding from hydrogels with increasing sucrose concentration. This was unexpected because when feeding from liquid droplets, L. humile increases feeding time with increasing sucrose concentration, 18 as do other ant species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ingestion volume from hydrogels decreased as sucrose concentration increased, consistent with results of L. humile and other ant species feeding from liquid droplets. 18,23,24 However, ants spent less time feeding from hydrogels with increasing sucrose concentration. This was unexpected because when feeding from liquid droplets, L. humile increases feeding time with increasing sucrose concentration, 18 as do other ant species.…”
Section: Discussionmentioning
confidence: 99%
“…18,23,24 However, ants spent less time feeding from hydrogels with increasing sucrose concentration. This was unexpected because when feeding from liquid droplets, L. humile increases feeding time with increasing sucrose concentration, 18 as do other ant species. [23][24][25] The intake rate (volume ingested in a given time) remained constant until the sucrose concentration was 40%, after which the intake rate reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although carbohydrates are central resources for the ants, since the need for sugary sources may affect their behavior, from the interspecific interaction to the collective decision-making (e.g. Grover et al, 2007;Arganda et al, 2014;Sola & Josens, 2016;Frizzi et al, 2018;Wittman et al, 2018), an interesting improvement of the study would be to repeat the experiment with foods rich in fats or proteins, maybe including some different indicators in the analysis, such as hormone secretion, frequencies of trophallaxis and recruitment behavior. Moreover, we selected these experimental solutions on the basis of previous studies, which showed a clear scalar response of workers.…”
Section: Discussionmentioning
confidence: 99%
“…Trophallactic feeding with fruit juices could provide a separate stimulus for fruit harvesting. Sugar concentration of solutions distributed through trophallaxis affects recruitment of foragers in Linepithema humile (Sola & Josens, ), and fruit odours could be used by recruits to target berries rather than leaves (cf. odour‐based targeting in Camponotus mus ; Provecho & Josens, ).…”
Section: Discussionmentioning
confidence: 99%